High-performance liquid sensor based one-dimensional phononic crystal with demultiplexing capability. (March 2021) - Zaki, Shrouk E.; Mehaney, Ahmed; Hassanein, Hekmat M.; Aly, Arafa H.
Highlights: 1D phononic crystal used as Demultiplexing liquid sensor with high sensitivity records. 1D phononic crystal with more than one cavity has a significant role regarding the sensor performance. More than one liquid can be simultaneously detected using smart Demultiplexing sensor design. Abstract: In this paper, a novel design of a one-dimensional defected phononic crystal (1D-DPC) sensor as a demultiplexer for sensing and distinguishing different harmful liquids is presented. The liquids of interest are acetone, ethanol, methanol, chloroform, phenol, 1-propanol, and mercury. Firstly, the liquids have been added in a single cavity inside the 1D-DPC design. Different resonance peaks related to each liquid appeared in the center of the phononic bandgap, each resonance frequency changes as the liquid type alters. Secondly, we examined the ability of the 1D-DPC liquid sensor to detect different concentrations of ethanol. Thirdly, the acetone, ethanol, methanol, chloroform, and mercury liquids at the same time via the 1D-DPC demultiplexer design. The performance parameters such as sensitivity, quality factor, and figure-of-merit on the 1D-DPC demultiplexer were calculated as well. The numerical investigations of the PC are studied based on the transfer matrix method. In the case of the 1D-DPC demultiplexer, liquid gives the highest sensitivity and FOM of 2.07 MHz/(kg/m 3 ) and 2780 m 3 /Kg, respectively for ethanol. Meanwhile, the 1D-DPC liquid sensitive sensor the highest sensitivity and FOM were obtained for methanol of 0.245 MHz/(kg/m 3 ) and 252 m 3 /Kg, respectively. The proposed 1D-DPC demultiplexer liquid sensor showed higher sensitivity compared with previous 1D-DPC liquid sensors. Moreover, we studied the damping rate effect on the resonant peaks of the 1D-DPC demultiplexer liquid sensor. Finally, our obtained results succeeded for the first time to couple both the 1D-DPC liquid sensor and the 1D-DPC demultiplexer in the same design with high performance. The proposed 1D demultiplexer idea can open the door to an entirely new type of liquid sensing modality in the simple 1D PC designs for many industrial and technological applications.